The evolutionary ecology of extremophile fishes from hypersaline lakes, caves, and toxic streams - Wilson, Elizabeth Jane (Kansas State University, 2024)
Transitions of organisms across habitat boundaries are widespread in nature. Studying such transitions can provide insight into how biodiversity arises as organisms undergo phenotypic and ecological changes when they adapt to novel environmental pressures. Furthermore, systems in which populations independently colonize novel environments with similar selective forces allow for investigating the predictability of biological processes. For my dissertation, I leveraged four systems of extremophile fishes to make comparisons across multiple populations that have overcome similar environmental stressors. (1) I analyzed patterns of differential gene expression between a freshwater and a hypersaline population of a livebearing fish, Limia perugiae, and compared these gene expression patterns to other pairs of freshwater and saltwater populations of other fish species to understand if mechanisms of osmoregulation are shared among teleost fishes. I found key differentially expressed genes underlying salinity transitions in L. perugiae, but there was little evidence for convergence in gene expression across lineages, suggesting that—at least at the level of gene expression—fish use different mechanisms to overcome salinity barriers. (2) I conducted a study of the natural history and trophic ecology of Astyanax mexicanus, a tetra that has colonized multiple caves in Mexico. I found that cavefish had substantial variation among cave populations in body size, sex ratios, and patterns of resource exploitation. But even though cavefish consume a broad array of resources, they still experience nutrient limitation during both the rainy and dry seasons, contradicting the previously held assumption that they experience intermittent starvation. (3) I tested how repeated colonization of toxic sulfide springs has driven changes in host-microbiome associations of a species of livebearing fish, Poecilia mexicana. I found convergence in the microbiomes of sulfidic P. mexicana across four replicate drainages, as well as shared core microbes among the sulfidic lineages that constitute candidate microbes for future research on their potential role in adaptive symbioses. (4) I leveraged 23 populations of livebearing fishes that broadly vary in their ecology to investigate what factors shape host-associated microbiomes and to test in an explicit phylogenetic context whether repeated adaptation to sulfide springs results in microbiome convergence. I found that the microbiome dissimilarity between lineages was correlated with the environmental microbiome dissimilarity and the host’s phylogenetic distance, indicating that the environment and the host’s evolutionary history contribute to host microbiome assembly. I further found microbiome convergence among the sulfidic lineages, demonstrating that shared physiochemical stressors drive convergent associations between hosts and their microbial communities. Overall, my dissertation provides insight into the commonalities and differences in how populations respond to novel sources of selection in extreme environments, which has broad implications for understanding patterns of biodiversity and the predictability of biological processes.
Keywords: Evolution; Ecology; Fish; Microbiome